(untitled) (Archive of Conferences, 2020)
The main trends in the development of the modern economy include the increase in the share of the non-productive sector through the development of Information Technologies, the improvement of the quality content of the material and technical base of the production sector, socio-economic processes based and oriented to active information cooperation, the development of the telecommunications services market, its complexity